Pengaruh Pemberian Tablet Tambah Darah terhadap Kadar Hb pada Siswi yang Menderita Anemia di SMA Negeri 1 Tambakboyo Tuban - Diah Eko M; Heny Ekawati; Siti Naimatun Nisa (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Iron deficiency anemia (ADB) is anemia that arises due to reduced iron supply for erythropoiesis, due to empty iron stores (depleted iron stores) which ultimately results in reduced hemoglobin formation. This study aims to determine the effect of giving blood supplement tablets on HB levels in female students suffering from anemia at SMAN 1 Tambakboyo, Tuban Regency. The research design used a pre-experiment using a one group pre test post test approach, with a total sampling technique on a population of 34 female students suffering from anemia in class X and analyzed using the Wilcoxon test. The instruments in this research were Standard Operating Procedures (SOP), hemoglobin level observation sheets and Easy Touch GCU brand hemoglobin measuring equipment. The results of the study showed that the average HB level before 10.17 g/dl and after 15.46 g/dl given blood supplement tablets was normal. The results of the Wilcoxon test obtained a significant value of p=0.000 (p<0.05), which means that there was a significant difference in the HB levels of class X female students before and after being given blood supplement tablets. Health workers, especially in school health offices, should provide blood supplement tablets at the right time so that female students can take the blood supplement tablets regularly and finish them.